(untitled) (Defense and Security Studies, 2025)
This review explores the security challenges and solutions associated with Wireless Sensor Networks (WSNs). It provides a comprehensive analysis of common security threats, including various types of attacks and their potential impacts on WSNs. The paper discusses critical security requirements such as data integrity, authentication, and secure communication, and examines defensive measures to mitigate these threats. Additionally, the review addresses trust management within WSNs, highlighting the importance of establishing reliable and secure networks. Emerging trends such as the integration of artificial intelligence, blockchain technology, quantum cryptography, edge computing, and secure multi-party computation are also discussed, showcasing the latest advancements aimed at enhancing WSN security. The findings underscore the necessity for ongoing research and development to improve the security and efficiency of WSNs, ensuring their viability for diverse applications.